Static composting of cow manure and corn stalk covered with a membrane in cold regions - Shi, Fengmei; Xu, Chengjiao; Liu, Jie; Sun, Fang; Yu, Hongjiu; Wang, Su; Li, Pengfei; Yu, Qiuyue; Li, Dan; Zuo, Xin; Liu, Li; Pei, Zhanjiang (Frontiers in Bioengineering and Biotechnology, 2022)
The disposal of livestock wastes is an urgent task in China. Compost is highly regarded for its ability to treat livestock wastes and to protect arable land. In particular, some problems of livestock manure in cold regions such as low efficiency because of low environmental temperature in winter urgently needs to be solved. In order to provide valuable composting information in cold area at low environmental temperature, the composting experiments were carried out with cow manure and corn stalk as substrates. The properties and bacterial community of compost samples in different stages were investigated. The electric conductivity (EC), total nitrogen (TN), total phosphorus (TP) and organic matter (OM) of the final compost were 551 μS/cm, 1.12% , 0.77% and 63.5%, respectively. No E. Coli or Ascaris eggs were detected. Temperature was the key factor to affect the physical-co-chemical and biological properties. The absolutely dominant genus is Sporosarcina, Virgibacillus, Flavobacterium and Steroidobacte in heating, high temperature, cooling and maturing stage, respectively. And these bacteria could act as biological indicators during composting process. Cryobacterium, Caldicoprobacter, Virgibacillus, Sporosarcina were relatively novel genera in the compost piles in cold environment. The biodegradation of exogenous substances mainly occurs in the initial and maturing stages. It is proved that the composting can be carried out successfully in early spring or later autumn after harvest.